Sorafenib for the treatment of hepatocellular carcinoma with portal vein tumour thrombosis: a systematic review of comparative studies - Qi, Xingshun; Guo, Xiaozhong (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Sorafenib is the first-line treatment of choice for advanced hepatocellular carcinoma (HCC). However, the benefits of sorafenib in HCC patients with portal vein tumour thrombosis (PVTT) remain uncertain. Until now, a total of eight comparative studies have been identified for this systematic review. Four retrospective studies showed that hepatic arterial infusion chemotherapy, hepatic resection, and three-dimensional conformal radiotherapy might be superior to sorafenib in improving the overall survival. Two ongoing randomised controlled trials (RCTs) will compare the outcomes of transarterial chemoembolisation or radioembolisation with those of sorafenib for the treatment of HCC with PVTT. In addition, two completed RCTs found that additional use of cryotherapy or radiofrequency ablation could prolong the survival of patients receiving sorafenib. In conclusion, the clinical efficacy of sorafenib in HCC patients with PVTT has been widely challenged by other interventions. However, further well-designed RCTs are necessary to confirm the findings of retrospective analyses. Cryotherapy or radiofrequency ablation may be considered as an adjunctive therapy in such patients, if sorafenib is prescribed.